Reflections on article 362 of the Code of Criminal Procedure (Revista do Tribunal Regional Federal da 3ª Região, 2017)
The aim of this work is to demonstrate that the summons at a specific time in Brazilian criminal proceedings process represents a legislative advance and it is justifiable to extend it to summonses as well, given the the common reasons behind it.
Keywords: Broad defense; summonts at a specific time; premeditated concelament; knowledge of the claim by premise; silence as a defense option; subpoena by time